Robusta Coffee (Coffea robusta L.) seed germination response in various plant natural growth regulators with soaking duration - Yeni Noviana; Meiriani; T. Irmansyah (Jurnal Online Pertanian Tropik, 2022)
One of causes coffee germination process takes a long period of time, because of the caffeine contained in coffee beans can inhibit the activity of amylase enzyme plays a role in the coffee germination process. Therefore, a study was conducted on the provision of Natural Growth Regulatory Substances (Natural PGR). This research was conducted at the Green House, Faculty of Agriculture, Univeritas Sumatera Utara, Medan from October 2019 to January 2020 using a Randomized Block Design (RBD) with two treatment factors : Factor 1 Natural PGR: A0 (water), A1 (bamboo shoot extract), A2 (shallot extract), and A3 (bamboo shoot extract + shallot extract). Factor 2 soaking duration : L1 (6 hours), L2 (12 hours), and L3 (18 hours). The results showed that the application of natural growth regulators (bamboo shoot extract or shallot extract) significantly increase the germination rate and seed vigor index. Soaking durationof 18 hours significantly increase presentation of germination but not different significantly from soaking for 12 hours, but there was no interaction between the two treatment factors. Keywords: Germination, Robusta coffee, natural PGR, soaking duration